Psycholinguistics and Language Learning in the 21st Century: Theoretical and Empirical Perspectives - Mantasiah Mantasiah; Sry Wahyuni; Ita Sarmita Samad (Majesty Journal, 2026)
Background. Psycholinguistics plays an important role in explaining how individuals acquire, process, understand, and produce language through various cognitive mechanisms. Purpose. This study aims to examine the role of psycholinguistics in language learning and language development by integrating theoretical foundations and recent empirical findings. Methods. It employed a literature review method using data from peer-reviewed journal articles published between 2020 and 2025, as well as seminal books and theoretical works in psycholinguistics relevant to the topic. The selected literature focused on language learning, language acquisition, cognitive processes, social interaction, affective factors, and digital technology in language education. Data were analyzed descriptively and critically to identify major concepts, research trends, and practical implications. Results. The findings indicate that language learning is influenced by the interaction of cognitive, social, and affective factors. Working memory, attention, and information processing contribute significantly to language acquisition, while social interaction and positive affective conditions support language development and communicative competence. Empirical evidence also demonstrates that digital technologies enhance cognitive engagement, vocabulary retention, and personalized learning experiences. Conclusion. The study concludes that psycholinguistics serves not only as a theoretical framework for understanding language processes but also as a practical foundation for developing effective, adaptive, and learner-centered language learning strategies in the digital era.